Compatibility of sportswomen at a selection in commands on group exercises of calisthenics taking into account their technical and special physical preparedness - O.S. Kozhanova (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Efficiency of selection is grounded in commands on group exercises of calisthenics taking into account motive compatibility of sportswomen. It is assumed that motive compatibility of gymnasts will be the leading factor of increase of effectiveness of competition activity of command. 40 students took part in research. 56 trainers took part in the questionnaire questioning. It is suggested to carry out completing of commands on the basis of complex estimation of similarity of level of technical and physical preparedness of sportswomen. It is set that from 40 highly skilled gymnasts 68 % had a level of physical and technical preparedness above average. In preferable composition of command 13 sportswomen entered with the greatest indexes on the criterion of motive compatibility. It is set that motive compatibility is a meaningful criterion at a selection in commands on group exercises of calisthenics.